2006
DOI: 10.2136/sssaj2005.0099
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dioxide Emissions from Exhumed Petrocalcic Horizons

Abstract: The second largest pool of terrestrial carbon is soil CaCO 3. In addition to being an important sink of atmospheric CO 2 , soil carbonate is potentially an important source of atmospheric CO 2. The cemented form of soil carbonate-the petrocalcic horizon-develops in geomorphically stable soil in arid, semiarid, and some subhumid climates. In many of these dryland areas, such as the Chihuahuan Desert of North America, erosion has stripped away overlying soil and exhumed the petrocalcic horizon, thereby exposing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 34 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…The soils at Corral Pocket are high in inorganic carbon [ Bowling et al , 2010; Goldstein et al , 2005], and soil carbonates may play a role in short‐term CO 2 dynamics in arid soils [ Serrano‐Ortiz et al , 2010]. However, the δ 13 C of CO 2 evolved from calcite precipitation would be more enriched (less negative) than the C 4 range [ Serna‐Perez et al , 2006; Stevenson and Verburg , 2006].…”
Section: Discussionmentioning
confidence: 99%
“…The soils at Corral Pocket are high in inorganic carbon [ Bowling et al , 2010; Goldstein et al , 2005], and soil carbonates may play a role in short‐term CO 2 dynamics in arid soils [ Serrano‐Ortiz et al , 2010]. However, the δ 13 C of CO 2 evolved from calcite precipitation would be more enriched (less negative) than the C 4 range [ Serna‐Perez et al , 2006; Stevenson and Verburg , 2006].…”
Section: Discussionmentioning
confidence: 99%
“…Only a process, such as soil acidification, causing CaCO 3 dissolution could cause carbonates to become a source of global carbon. Recently, Serna-Perez et al (2006) concluded that exhumed petrocalcic horizons are not emitting significantly more CO 2 than adjacent soils. Therefore, soil CaCO 3 can be considered a recalcitrant reservoir for carbon sequestration, which is consistent with our modeling simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that N is often the most limiting plant nutrient in terrestrial ecosystems, NO À 3 in desert soils often accumulates to highest concentrations at depth (1-5 m) (Hartsough et al, 2001;Marion et al, in press;Stokstad, 2003;Wallace et al, 1978;Walvoord et al, 2003), rather than near the surface (Jobbagy and Jackson, 2001). Another example is the potential role that CaCO 3 deposition may play in desert soils as a sink for and possibly as a source of atmospheric CO 2 (Capo and Chadwick, 1999;Monger and Gallegos, 2000;Schlesinger, 1982;Serna-Perez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These are potentially a major problem in modeling biocrust-derived C fluxes. The large differences between modeled respiration (see Castillo-Monroy et al 2011) and NPP for desert biocrusts shows that the calculated NPP will be very sensitive to non-biocrust-derived C. However, the literature indicates that abiotic fluxes from soil carbonates, the obvious potential source of C flux from soils, can be very low (Serna-Perez et al 2006; although see Rey 2015). A combination of the datasets accumulated in the SCIN project ) with the current knowledge regarding CO 2 fluxes in biocrusts from arid and semiarid environments will allow modeling the behavior of these communities in a global change scenario ( Fig.…”
Section: Proposed Methodologies On the Microscalementioning
confidence: 99%